Proposed Coastal Cities Environmental Sanitation Project--Viet Nam : Public-Private Partnerships for Solid Waste and Septage Management - World Bank (World Bank, Washington, DC, 2019)
A solid waste management (SWM) preparation mission was carried out mid-2004 for the World Bank Coastal Cities Environmental Sanitation Project (CCESP). The purpose of the mission was to assess the SEM needs of the cities of Dong Hoi, Nha Trang, and Quy Nhon over a fifteen-year planning horizon, taking into account the quantity, character, and distribution of solid wastes, disposal alternatives and management systems governing administration and finance. The World Bank is now supporting a consultancy, the objectives of which are to present a range of options for use of the private sector in solid waste collection and septage management, to agree a preferred approach for each CCESP city, and then to develop a detailed implementation program. The consultancy is to be conducted over two separate trips to the three project cities. The first trip was conducted between 13 and 30 September, 2005 and included a visit to Da Nang to discuss private sector participation initiatives introduced in that city as part of the World Bank’s Three Cities Sanitation Project. This paper presents the initial findings of the public-private partnership (PPP) consultancy team and addresses each key activity. The findings of the visit to Da Nang are also included in this paper.